Geoprocessing applied in morphometric of the Ribeirão do Veado watershed - Piratininga (SP), seeking the conservation of the water resources - Felipe, Andrea Cardador [UNESP]; Campos, Sergio [UNESP]; Parizoto, Nathalia Maria Salvadeo Fernandes [UNESP]; Nardini, Rafael Calore [UNESP]; Traficante, Daniela Polizeli [UNESP] (GN1 Sistemas e Publicacoes, 2013)
The planning of the soil use has been turned out to be a very important activity in the agricultural and socioeconomic development, because the inadequate use and without planning of the lands it causes low yield of the crops. This work aimed the morphometric characterizatiwon of the Ribeirão do Veado watershed - Piratininga (SP), tributary of the Rio Batalha, seeking the planning of conservation practices of the soil in the area, through geoprocessing. The watershed with 1776 ha, is located in the geographical coordinates 22o 23’ 32” to 22o 26’ 17” of latitude S and 49o 06’ 34” and 49o 09’ 45” of longitude W Gr. It was used as cartographic base the Map of Brazil (IBGE, 1973), in scale 1:50000. The dimension variables analyzed were: larger length (C), area (A) and perimeter (P) of the watershed and the for the relief were: medium altitude (Hm), altimetric width (Ha), medium steepness (H), form factor (Ff), relief reason (Rr) and drainage density (Dd), measured through the System of Geographical Information - Idrisi Java. The results showed that the medium steepness allowed classifying the relief as wavy, probably, due to the substratum that has high permeability with larger rain water infiltration and superficial drainage of the water, conserving the soil. The form factor (0.38) and the drainage density (1.66 km km- ²) allowed to conclude that probably the watershed is not subject the flood, once the relief presents high influence on the hydrological factors. Therefore, the knowledge of the area hydrology and relief is of fundamental importance in the decision taking of planning actions and administration in the future preservation.

La planificación del uso de la tierra se está convirtiendo en una actividad muy importante en los sectores agrícola y socio- económico, ya que el uso inadecuado de la tierra ocasiona bajos rendimientos de los cultivos. Este estudio tuve como objetivo la caracterización morfometrica de la cuenca del Ribeirão do Veado - Piratininga (SP), un tributario del río Batalha, visando planificación de las prácticas de para la conservación de suelos en el área, a través de Geoprocesamiento. La cuenca con 1776 ha, está situada entre las coordenadas geográficas 22° 23' 32" y 22° 26' 17" de latitud S y 49° 06' 34" y 49º 09' 45" de longitud W Gr. Fue utilizado como base geográfica el Carta del Brasil (IBGE, 1973) en escala 1:50000. Las variables dimensionales evaluadas fueron: mayor longitud (C), área (A) y el perímetro (P) de la cuenca y as de lo relieve: altitud media (Hm), amplitud altimétrica (Ha), la pendiente media (H), el factor de forma (Ff), relación de relieve (RR) y densidad de drenaje (Dd ), medidos mediante el sistema de Información Geográfica - Idrisi Java. Los resultados mostraron que la declividad media de pendiente permite clasificar el relieve como ondulado, probablemente debido al sustrato que tiene una alta permeabilidad con una mayor infiltración de agua de la lluvia y el escurrimiento superficial del agua, manteniendo el suelo. El factor de forma (0,38 ) y la densidad de drenaje (1,66 km km² ) permitieron la conclusión de que, probablemente, la cuenca no está sujeto a las inundaciones, ya que el relieve muestra una gran influencia sobre los factores hidrológicos. Por lo tanto, el conocimiento de la hidrografía y relieve de la zona es de importancia fundamental en la toma de acciones de planificación y gestión en la conservación futura.

O planejamento do uso do solo vem se tornando uma atividade muito importante no desenvolvimento agrícola e sócioeconômico, pois o uso inadequado e sem planejamento das terras provoca a baixa produtividade das culturas. Este trabalho objetivou a caracterização morfométrica da microbacia do Ribeirão do Veado – Piratininga (SP), afluente do Rio Batalha, visando o planejamento de práticas de conservação do solo na área, através de geoprocessamento. A microbacia com 1776 ha, situa-se entre as coordenadas geográficas 22o 23’ 32” a 22o 26’ 17” de latitude S e 49o 06’ 34” a 49o 09’ 45” de longitude W Gr. Foi utilizado como base cartográfica a Carta do Brasil (IBGE, 1973), em escala 1:50000. As variáveis dimensionais analisadas foram: maior comprimento (C), área (A) e perímetro (P) da microbacia e as do relevo: altitude média (Hm), amplitude altimétrica (Ha), declividade média (H), fator de forma (Ff), razão de relevo (Rr) e densidade de drenagem (Dd), medidas através de do Sistema de Informações Geográficas – Idrisi Java. Os resultados mostraram que a declividade média permitiu classificar o relevo como ondulado, provavelmente, devido ao substrato que tem alta permeabilidade com maior infiltração da água das chuvas e escoamento superficial da água, conservando o solo. O fator de forma (0,38) e a densidade de drenagem (1,66 km km- ²) permitiu concluir que provavelmente a microbacia não é sujeita a inundação, uma vez que o relevo apresenta grande influencia sobre os fatores hidrológicos. Portanto, o conhecimento da hidrografia e do relevo da área é de fundamental importancia na tomada de ações de planejamento e gestão na preservação futura
Geoprocesamiento aplicado en la morfometria de la cuenca del Ribeirão do Veado - Piratininga (SP), buscando la conservación de los recursos hídricos
Geoprocessamento aplicado na morfometria da microbacia do Ribeirão do Veado - Piratininga (SP), visando a conservação dos recursos hídricos
Keywords: Morphometric; Dimensional variables; Relief variables; Morfometria; Variables dimensionales; Variables de alivio; Morfometria; Variáveis dimensionais; Variáveis de relevo